The invention of wings : a novel - Kidd, Sue Monk (Viking, 2014)
"The story follows Hetty "Handful" Grimke, a Charleston slave, and Sarah, the daughter of the wealthy Grimke family. The novel begins on Sarah's eleventh birthday, when she is given ownership over Handful, who is to be her handmaid and follows the next thirty-five years of their lives"--Provided by publisher.